Factors influencing consumers’ adoption of Islamic mobile banking services in Malaysia: an approach of partial least squares (PLS) - Mohd Thas Thaker, Mohamed Asmy; Allah Pitchay, Anwar; Mohd Thas Thaker, Hassanudin; Amin, Md Fouad (Emerald Group Publishing Ltd., 2019)
Purpose – This paper aims to test the factors that can influence the adoption of Islamic mobile banking services among the current users in Malaysia. Design/methodology/approach – A sample of 250 current users of Islamic mobile banking services provided opinions about their intention to adopt Islamic mobile banking services. Later, the data are analysed using partial least squares approach. Findings – Perceived usefulness and risk are the factors that influence the intention to adopt Islamic mobile banking services among the existing users. Research limitations/implications – There are some limitations of the current study. The sample size and area of study becomes the obvious limitations. Thus, there is a need for caution in the interpretation of the results and the conclusion cannot be as generalised. Besides, the use of current factors might limit the ability to explore other potentially important determinants of the users. Thus, future research can be conducted by incorporating new factors and provide new insights for Islamic mobile banking services. In addition, the sample is biased towards people who are currently using mobile banking services. Practical implications – By understanding these factors among the customers, it would help the industry player, particularly Islamic financial institutions to plan and strategise appropriate policies and support necessary programme on diversifying and promoting financial transaction using mobile banking services among their existing and potential customers. Originality/value – This paper offers an additional literature on Islamic mobile banking, especially from the Malaysian context. There is a lack of study that focusses on Islamic mobile banking services. The paper is considered to be the first attempt to examine factors that influence Malaysian Islamic banking customers to adopt Islamic mobile banking services, which is not often considered in previous studies